EVALUASI MUTU BERAS DAN PENERAPAN GOOD HANDLING PRACTICE (GHP)) DAN GOOD MANUFACTURING PRACTICE (GMP) (STUDI KASUS PENGGILINGAN PADI DI KABUPATEN KARAWANG) - Ekaterina Setyawati; Sukardi; Yandra Arkeman; Muslich (Department of Agroindustrial Technology, Bogor Agricultural University, 2020)
Rice is still a strategic commodity in Indonesia, because it is still a staple food for most of Indonesia's population. Fulfillment of production must also be accompanied by aspects of quality fulfillment. This study aimed to evaluate the quality of rice and to evaluate the application of Good Handling Practice (GHP) and Good Manufacturing Practice (GMP) in small and medium rice miling in Karawang Regency. The performance of rice quality was evaluated based on the requirements for the rice quality class from the Minister of Agriculture Regulation Number: 31/Permentan/PP.130/8/2017 which includes water content, head rice, broken grains and whiteness degrees. Based on the results of quality of rice, it was found that the water contents in the medium and premium quality were 64% and 27%, respectively. Based on the criteria for quality of head rice, it was obtained that all samples were not included premium quality and 22.2% in medium quality. For the criteria of broken grains, it was found 36% in medium quality and the other were below the quality standard. Meanwhile, based on the whiteness degree, most of the rice samples were included in the medium and premium rice qualities. The applications of GHP in rice milling were 42% for small rice milling and 50% for medium rice milling, whereas applications of GMP were 69% for small rice milling and 92% for medium rice milling. Lack of socialisation regarding the importance of quality and implementations of GHP and GMP, and cost of risk that must be added by implementing GMP and GHP were factors caused the low quality of rice in Karawang Regency.Keywords: rice quality in Karawang district, GHP, GMP